Long-term data prove useful to keep track of non-indigenous seaweed fate - Petrocelli, Antonella; Wolf, Marion Adelheid; Sciuto, Katia; Sfriso, Adriano; Rubino, Fernando; Ricci, Pasquale; Cecere, Ester (Frontiers in Environmental Science, 2023)
The present paper deals with the results of eleven-year monitoring activity on non-indigenous species (NIS) of seaweeds, which was performed in the Mar Piccolo of Taranto (southern Italy, Mediterranean Sea), a site of the European LTER network. The Mar Piccolo is a transitional water system, where a century-old intensive mussel farming activity has been carried out, together with an intense import-export business of bivalve mollusks. Previous studies showed that this basin is third for NIS seaweed introduction in the Mediterranean Sea, after the Thau Lagoon and the Venice Lagoon. In the studied period (2011-2021), two different time frames (i.e., 2011-2015 and 2016-2021) were considered, since they were based on a different number of sampling sites. To investigate spatial and temporal differences in the seaweed assemblage, a multivariate analysis was performed considering the NIS and the most important native species in terms of temporal occurrence. Fourteen NIS were recorded in total in the Mar Piccolo of Taranto during this period, with variable abundances among sites and years: nine species in the first time period, and thirteen species in the second one. Caulerpa cylindracea, recorded with negligible biomass in the first period, was absent in the second-period samplings. Molecular analyses confirmed the taxonomy of three species (i.e., Grateloupia minima, Neopyropia koreana, Polysiphonia morrowii), previously identified only through morphological features. The most abundant species was Hypnea corona, which almost doubled its biomass in the second time period compared to the first one. Three species (i.e., Caulacanthus okamurae, G. minima, and P. morrowii) increased their biomass by an order of magnitude in the second time period. No significant differences were found over years. Site 1 resulted in significant differences among the sites and different seasonal pattern occurred among the investigated sites. No significant long-term changes occurred in the seaweed assemblages, suggesting the absence of strong disturbances due to the settlement of NIS.